Development of Virtual Reality Application on Pineapple Farm Exploration: PinExplore VR - Mohammad Faiz, Muhammad Adib; Suparjoh, Suriawati (Applied Information Technology And Computer Science, 2025)
Virtual reality technology is now commonly employed to replicate the actual world in several businesses. Virtual reality technology is typically utilised for both agricultural education and enjoyment. Nonetheless, young farmers who wish to learn how to grow pineapples frequently employ old methods. Furthermore, by not utilising the available technologies for training, the learning approach is less successful. Thus, PinExplore VR, an agricultural exploration software that fully utilises virtual reality technology, will be created for the Windows operating system. Target users for this project are public aged 20 to 30 years old.  The PinExplore VR application was developed using the Prototyping model methodology. The user should find this application entertaining and useful in imagining risk-free pineapple cultivation. The SUS approach will be used for testing and evaluation in order to determine whether usability is acceptable. The Acceptability Ranges of the average score is 70.63, which in the “acceptable” range and “Good” is the adjective rating. In the nutshell, the target users are satisfies with the application.